Pronunciation Can Be Acquired Outside the Classroom: Design and Assessment of Homework‐Based Training - MARTIN, INES A. (The Modern language journal (Boulder, Colo.), 2020)
Even though there is ample evidence that pronunciation plays a crucial role in effective second language (L2) communication, pronunciation training is frequently neglected in L2 classrooms due to time constraints or because instructors do not feel adequately prepared to teach pronunciation. To address this discrepancy, the present study investigates the effectiveness of a novel, homework‐based method of pronunciation instruction. Novice German learners’ (N = 122) perception and oral production skills on the word and sentence level were assessed at the beginning and the end of the semester. Learners were assigned to 1 of 3 groups: a homework‐based pronunciation training group, an in‐class training group, and a control group. The results showed that the learners in the homework training group significantly outperformed learners in the control group on some (but not all) measures of phonological perception skills and on comprehensibility measures of productions of individual words. Results further revealed no significant difference between learners who received homework‐based or in‐class pronunciation training and responses on a debriefing questionnaire showed that learners were equally satisfied with both training modalities. Taken together, these results suggest that homework‐based pronunciation training is similarly effective as in‐class practice.